Innovation and Regional Growth in the European Union - Crescenzi, Riccardo; Rodriguez-Pose, Andres; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book investigates the EU's regional growth dynamics and, in particular, the reasons why peripheral and socio-economically disadvantaged areas have persistently failed to catch up with the rest of the Union. It shows that the capability of the knowledge-based growth model to deliver its expected benefits to these areas crucially depends on tackling a specific set of socio- institutional factors which prevents innovation from being effectively translated into economic growth. The book takes an eclectic approach to the territorial genesis of innovation and regional growth by combining different theoretical strands into one model of empirical analysis covering the whole EU-25. An in-depth comparative analysis with the United States is also included, providing significant insights into the distinctive features of the European process of innovation and its territorial determinants. The evidence produced in the book is extensively applied to the analysis of EU development policies
1 Introduction -- 2 Theoretical Frameworks: A Spatial Perspective on Innovation and the Genesis of Regional Growth -- 3 Geographical Accessibility and Human Capital Accumulation -- 4 The Role of Underlying Socio-Economic Conditions -- 5 Knowledge Flows and Their Spatial Extent -- 6 Innovation in an Integrated Framework: A Europe-United States Comparative Analysis -- 7 What Can We Learn from the "Integrated Approach" to Regional Development? The Impact of EU Infrastructure Investment -- 8 EU Development Policies and the Socio-Economic Disadvantage of European Regions -- 9 Conclusions -- References -- Appendices
Electronic reproduction.
Keywords: Regional economics; Economic geography; Electronic books; European Union countries -- Economic conditions; European Union countries -- Economic policy